Prospect Convenient Steadfast Procedure in Wireless Sensor Network - Jewan Singh; Vibhakar Mansotra (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This article objective is to improve the steadfast routing in Wireless Sensor Networks with little interfering and avoid packet collision. In the scheme, the entire node has the option of electing next Data Communication Node (DCN). The next data communication node is chosen depend on the intensity of link, remaining energy, and the node with distance towards the Base Station. Thus, the sender node transmits the information to the best DCN. Instantly, the DCN sends the acknowledgement (ACK) along with the number of packets received back to the node from which it obtains the data. The sender node assures the delivery of the transmitted packets by comparing the value of number of packets sent with the value obtained with the acknowledgement. If they are equivalent, it will send the verification identity to the DCN. If it is not equivalent, it will decide another node with highest link intensity. After that, the data chooses the DCN and repeat the process until the data reaches the Base Station.